The blood bag plasticizer Di-2-Ethylhexylphthalate causes red blood cells to form stomatocytes, possibly by inducing lipid flip-flop - Melzak, Kathryn; Uhlig, Stefanie; Kirschhöfer, Frank; Brenner-Weiss, Gerald; Bieback, Karen (Transfusion medicine and hemotherapy, 2018)
Background: During storage of red blood cell (RBC) concentrates, the plasticizer di-2-ethylhexylphthalate (DEHP) that keeps the blood bags soft leaches out and can be taken up by the RBCs. DEHP is known to be beneficial for the RBC storage quality, but the molecular mechanisms of the action are unknown. - Methods: Aqueous suspensions of DEHP were added to RBCs in buffer. The morphological effects were observed on RBCs from 5 donors. Flow cytometry with annexin A5 binding was used to measure the exposed phosphatidylserine. - Results: DEHP induced the formation of stomatocytes at concentrations as low as ng/ml, provided that the cell suspension was also sufficiently dilute. Some spherocytes, which were susceptible to lysis, were also formed; after lysis, RBC ghosts were seen to continue the transition to the cup-shaped stomatocyte form. Incubation with DEHP increased the exposed phosphatidylserine, an effect that was also observed in the presence of vanadate, which inhibits the ATP-dependent translocases that maintain the membrane's lipid asymmetry. - Conclusions: DEHP can have an active effect on RBC shape, instead of just preventing the storage-related shape changes. The effect appears to be mediated by increased flip-flop of lipids between the leaflets of the RBC membrane.
Gesehen am 26.03.2020